Anthropometric profile, balance ability, reaction time and bone health status among horseback riding athletes in Kelantan - Ibrahim, Siti Salwa Suhaida Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The purpose of this research was to explain the differences in the anthropometric profile, balance ability, reaction time and bone health status between two different groups according to their physical activity i.e., sedentary group and equestrian athlete group. A total of 10 healthy participants aged 27.60 (±8.01) years old were selected to participate in this study. Participants were matched according to age then grouped into the sedentary group (n = 5) and horseback riding group (n = 5) based on their category. The measurements were performed in the Exercise and Sports Science laboratory. The parameters of body fat percentage, weight and BMI of participants were measured using a "body composition analyzer" (Omron diagnostic scale). Unipedal stance test (UPST) was performed with the eyes open and closed for both sides of the leg i.e., the dominant and non-dominant legs. The mean of three UPST tests was measured for all conditions. Two reaction tests were performed using the Human Benchmark Test namely The Reaction Time Test and The Aim Trainer Test. Bone speed of sound (SOS), a marker of bone density, were measured on the dominant and non-dominant tibial and radial using a bone sonometer. The p-value was set with a confidence interval value of 95%. In a Mann-Whitney test analysis, this study found that the horseback riding group had a lower body fat percentage than the sedentary group. The UPST results showed that there was no statistically significant difference either in the open or closed eye conditions for both dominant and non -dominant legs between the horseback riding group and the sedentary group. A significant difference in the bone speed of sound, SOS can be seen scientifically in the non-dominant part of the 'radius' of the arm and 'tibia' of the foot of the horseback riding group compared to the sedentary group. Based on the results, significant differences were found in the percentage of body fat, as well as radial and tibial SOS for non-dominant hands and legs. Physical activities such as horseback riding can affect the individual body by burning calories through riding activities and have a good effect on bone health although equestrian sports are categorized as non-weight bearing exercise. It is hoped that the results of this study can be applied to the development of specific training of equestrian athletes or as a reference source for recreational activities of equestrian riding as a selection of physical activities that benefit the body. It is hoped that the community will be more aware and act in changing the sedentary lifestyle to a more active lifestyle in the future.